Biomimetic electroactive polyimide with rose petal-like surface structure for anticorrosive coating application - W. F. Ji; C. W. Li; S. K. Yu; P. J. Chen; H. L. Chen; R. D. Chen; B. H. Chen; C. L. Hsu; J. M. Yeh (eXPRESS Polymer Letters)
In this work, an electroactive polyimide (EPI) coating with biomimetic surface structure of rose petal used in anticorrosion application was first presented. First of all, amino-capped aniline trimer (ACAT) was synthesized by oxidative coupling reaction, followed by characterized through Fourier transform infrared spectroscooy (FTIR), liquid chromatography – mass spcerometry (LC-MS) and proton nuclear magnetic resonance (1H-NMR) spectroscopy. Subsequently, as-prepared ACAT was reacted with isopropylidenediphenoxy-bis(phthalic anhydride) (BPADA) to give electroactive poly(amic acid) (EPAA). Moreover, poly(dimethylsiloxane) (PDMS) was used to be the soft negative template for pattern transfer from the surface of rose petal to the surface of polymer coating. The EPI coating with biomimetic structure was obtained by programmed heating the EPAA slurry casting onto the negative PDMS template. The anticorrosive performance of as-prepared biomimetic EPI coating was demonstrated by performing a series of electrochemical measurements (Tafel, Nyquist, and Bode plots) upon cold-rolled steel (CRS) electrode in a NaCl aqueous solution. It should be noted that the biomimetic EPI coating with <Í>rose petal-like structure was found to exhibit better anticorrosion than that of EPI without biomimetic structure. Moreover, the surface contact angle of water droplets for biomimetic EPI coating was found to be ~150°, which is significantly higher than that of EPI coating with smooth structure (~87°), indicating that the EPI coating with biomimetic structure reveals better hydrophobicity. The apparent mechanism for improved anticorrosive properties is twofold: (1) the biomimetic structure of EPI coating can repel water droplets. (2) electroactivity of EPI coating promotes the formation of densely passive layer of metal oxide on metallic surface.